Study of the prevalence of critical and conflict-prone points in facades. (May 2017) - Carretero-Ayuso, Manuel J.; Moreno-Cansado, Alberto; de Brito, Jorge
Abstract: Facades are one of the most important areas of buildings, where one can find a large quantity of interacting layers, with multiple critical points emerging. This study concerns the complaints made by users in court, resulting in a total of 1374 damages having been analysed and quantified, grouped in 17 different types. The various underlying causes (29 in total) were also determined, as well as the building types and elements in which anomalies occur most frequently. These damages were grouped by similarity, and their prevalence was calculated in order to inform technicians with regard to which aspects should be improved in both design and construction. Highlights: This paper studies a large database on anomalies found in building facades in Spain. This database resulted from court cases resulting from users' complaints. All damages and causes are characterized according to the existing construction types. The most recurring failures and damages are analysed in detail.